Second sialic acid‐binding site of influenza A virus neuraminidase: binding receptors for efficient release. (28th December 2020) - Du, Wenjuan; de Vries, Erik; van Kuppeveld, Frank J. M.; Matrosovich, Mikhail; de Haan, Cornelis A. M.
Abstract : Influenza A viruses (IAVs) are a major cause of human respiratory tract infections and cause significant disease and mortality. Human IAVs originate from animal viruses that breached the host species barrier. IAV particles contain sialoglycan receptor‐binding hemagglutinin (HA) and receptor‐destroying neuraminidase (NA) in their envelope. When IAV crosses the species barrier, the functional balance between HA and NA needs to be adjusted to the sialoglycan repertoire of the novel host species. Relatively little is known about the role of NA in host adaptation in contrast to the extensively studied HA. NA prevents virion aggregation and facilitates release of (newly assembled) virions from cell surfaces and from decoy receptors abundantly present in mucus and cell glycocalyx. In addition to a highly conserved catalytic site, NA carries a second sialic acid‐binding site (2SBS). The 2SBS preferentially binds α2, 3‐linked sialic acids and enhances activity of the neighboring catalytic site by bringing/keeping multivalent substrates in close contact with this site. In this way, the 2SBS contributes to the HA‐NA balance of virus particles and affects virus replication. The 2SBS is highly conserved in all NA subtypes of avian IAVs, with some notable exceptions associated with changes in the receptor‐binding specificity of HA and host tropism. Conservation of the 2SBS is invariably lost in human (pandemic) viruses and in several other viruses adapted to mammalian host species. Preservation or loss of the 2SBS is likely to be an important factor of the viral host range. Abstract : Influenza A viruses contain sialic acid (SIA) receptor‐binding hemagglutinin (HA) and receptor‐destroying neuraminidase (NA). The balance between HA and NA is adjusted to the SIA receptor repertoire of the host species. Besides a conserved catalytic site, NA carries a 2nd SIA‐binding site (2SBS). The 2SBS enhances the activity of the catalytic site and affects the HA‐NA balance. Conservation or loss of the 2SBS is associated with (changes in) host tropism.